Physical activity patterns among children and adolescents with mild-to-moderate chronic fatigue syndrome/myalgic encephalomyelitis - Amberly Brigden; Lucy Beasant; Esther Crawley; Russell Jago; Emma Solomon-Moore (BMJ Publishing Group, 2019)
Objective Chronic fatigue syndromemyalgic encephalomyelitis (CFS/ME) is relatively common among children and adolescents; however, little is known about the physical activity levels and patterns of this population. The aim of this study was to examine the underlying patterns of physical activity among youth with mild-to-moderate CFS/ME. Cross-sectional associations between physical activity patterns with self-reported physical function, pain, fatigue, anxiety and depression were also examined.Design Baseline cross-sectional data from the Managed Activity Graded Exercise iN Teenagers and pre-Adolescents randomised controlled trial.Patients Children and adolescents (aged 8-17 years) diagnosed with mild-to-moderate CFS/ME who wore an accelerometer for at least three valid weekdays.Analyses Latent profile analysis was used to identify physical activity patterns. Linear regression models examined associations between physical activity classes and self-reported physical function, pain, fatigue, anxiety and depression.Results 138 children and adolescents (72.5% females) had valid data. Overall, participants did less than half the government recommended level of physical activity for children and adolescents, but not all were inactive: three (2.2%) did more than 1 hour of physical activity every day, and 13 (9.4%) achieved an average of 60 min a day. Adolescents (≥12 years) were less active than younger children, but activity levels were similar between genders. Three latent classes emerged from the data: 'active', 'light' and 'inactive'. Compared with being 'inactive', being in the 'light' class was associated with greater self-reported physical function (10.35, 95% CI 2.32 to 18.38) and lower fatigue (−1.60, 95% CI −3.13 to −0.06), while being 'active' was associated with greater physical function (15.26, 95% CI 0.12 to 30.40), but also greater anxiety (13.79, 95% CI 1.73 to 25.85).Conclusions Paediatricians need to be aware that physical activity patterns vary widely before recommending treatment.Clinical trial registration ISRCTN registry: 23 962 803